Bio-Based Nano-Enabled Cosmetic Formulations for the Treatment of Cutibacterium acnes-Associated Skin Infections - Kristina Ivanova; Eva Ramon; Aleksandra Ivanova; Susana Sanchez-Gomez; Tzanko Tzanov (MDPI AG, 2023)
Acne is a common chronic skin condition with serious physical and psychosocial consequences. In some cases, the appearance of pimples, whiteheads, or blackheads on the face, neck, and back may lead to scarring, disfiguring, depression, frustration, and anxiety in patients. Current treatments rely on antibiotics to eradicate Cutibacterium acnes (C. acnes), the bacterium responsible for this skin condition. However, these approaches do not scavenge the reactive oxidative species (ROS) generated during disease development and raise concerns about the increase in antimicrobial resistance. In this study, an environmentally friendly and cost-effective self-assembly nanoencapsulation technology based on zein, a bio-based hydrophobic protein, was employed to produce multifunctional essential oil (EO)-loaded nanocapsules (NCs) with superior antioxidant and bactericidal activity toward C. acnes. The NCs displayed "smart" release of the active cargo only under the conditions that were conducive to acne proliferation on skin. Once incorporated into creams, the EO-loaded NCs led to a complete inhibition of C. acnes and demonstrated the capacity to scavenge ROS, thus preventing damage to human skin cells. The in vitro permeation studies revealed that the nanoformulated EO was able to penetrate through the epidermis, indicating its potential for the treatment of skin diseases, such as acne.